Confronting allergies: strategies for combating pollution and safeguarding our health - Pattanayak, Santanu; Dinda, Suman Kalyan; Hazra, Shreyasee; Mukhopadhyay, Rittwicka; Samanta, Samvabi; Dey, Shramalina; Manna, Dipak (Frontiers in Allergy, 2025)
Increasing evidence demonstrates a robust link between environmental pollutants and allergic reactions, with air and indoor pollution exacerbating respiratory allergies and climate change intensifying seasonal allergies. Comprehensive action, including government regulations, public awareness, and individual efforts, is essential to mitigate pollution's impact on allergies and safeguard public health and ecological balance. Recent findings indicate a strong correlation between environmental pollutants and allergic reactions, with air pollution from vehicular emissions and industrial activities exacerbating respiratory allergies like asthma and allergic rhinitis. Additionally, indoor pollutants such as mold and volatile organic compounds are significant triggers of allergic responses, especially among vulnerable populations. Furthermore, climate change, driven by pollution, is intensifying seasonal allergies due to altered weather patterns and increased pollen production. This review emphasizes the critical importance of addressing pollution and allergies, highlighting the growing concerns in contemporary society. This review highlights the urgent need to address pollution and allergies, emphasizing their increasing significance in modern society and outlining effective allergy management strategies.